Reaktualisa Fatwa Bahsul Masa'il Nahdlatul Ulama' Sebagai Solusi Problematika Hukum Islam (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
The Bahsul Masa'il Fatwa of Nahdlatul Ulama' (NU) is a product of collective ijtihad based on a classical Islamic scientific approach. This forum has made an important contribution to responding to various Islamic legal issues that Indonesian society faces. However, the dynamic development of the era demands a reactualization of the fatwa to make it more relevant to contemporary challenges. This article discusses the importance of reactualizing the Bahsul Masa'il fatwa as a solution to Islamic legal problems. This study uses a qualitative method with a literature study approach to related primary and secondary sources. The findings show that reactualization can be done through strengthening methodology, updating views in the Maqasid al-shari'ah corridor, and integration with local and global needs. This makes the NU fatwa more adaptive to the development of the era while maintaining its conformity with sharia principles.
Keywords: Reactualization; Fatwa; Bahsul Masa'il; Nahdlatul Ulama; Islamic Law